Psychosocial Adaptation of Breast Cancer Patients Based on The Roy Adaptation Model - Daniar Septianing Faradina; Dian Handayani; Fransiska Imavike (Universitas Aisyah Pringsewu, 2023)
Breast cancer is the highest type of cancer in the world in 2020. Cancer treatment has side effects that cancer patients at high risk of experiencing difficulties in adapting, both to themselves and psychosocially. There needs to be an approach with an appropriate theory to direct patients to be able to adapt, one of them is the Roy Adaptation Model (RAM) by Callista Roy. The purpose of this study was to analyze adaptive stimuli associated with psychosocial adaptation in breast cancer patients. This research is a correlational method with a cross-sectional approach. The sample used was breast cancer patients who met the inclusion criteria of 58 samples. Samples were taken using a quota sampling. The instrument used was a modified questionnaire from previous studies. Data analysis used chi-square and logistic regression test. The results of this study are that focal, contextual and residual stimuli have a relationship with psychosocial adaptation. Focal stimulus is the dominant adaptive stimulus that influences psychosocial adaptation with an OR of 8.6. Nursing interventions are needed to support the patient's adaptive psychosocial adaptation abilities such as the involvement of clinical psychologists, providing emotional, psychological support to reduce psychosocial impacts.